Moderation Effect Of Islamic Social Reporting On Influences Of Islamicity Performance Index On Financial Performance Of Islamic Banking - Ade Ponirah; Silfi Oktariyani; Gina Sakinah; Yesa Tiara Purnama Sari (JPS (Jurnal Perbankan Syariah), 2023)
This study aims to analyze the effect of the Islamicity performance index on financial performance through Islamic social reporting as a moderating variable. This research uses quantitative methods. This study used purposive sampling to take samples from a total population of 18 Islamic commercial banks (ICB) to obtain five representative ICB samples. The data source uses secondary data in the form of information originating from the official ICB website. Data analysis used multiple linear regression and moderated regression analysis (MRA). The results showed that the zakat performance ratio, Islamic income vs. non-Islamic income ratio, and Islamic social reporting did not affect financial performance. However, the profit-sharing ratio has a significant effect on financial performance. Islamic social reporting can moderate the effect of the profit-sharing ratio on financial performance. However, Islamic social reporting cannot moderate the variable zakat performance ratio and Islamic income vs. non-Islamic income ratio on financial performance. This research can complement existing research and be a reference for ICB management disclosing information to stakeholders by applying Sharia principles.